Study of the perpendicular self-assembly of a novel high-χ block copolymer without any neutral layer on a silicon substrate. Issue 7 (29th January 2019) - Zhang, Baolin; Liu, Weichen; Meng, Lingkuan; Zhang, Zhengping; Zhang, Libin; Wu, Xing; Dai, Junyan; Mao, Guoping; Wei, Yayi
Abstract : A novel type of high- χ block copolymer, polystyrene- block -polycarbonate (PS- b -PC), which contains an active –NH– group on the polymer backbone between the PS block and the PC block, has been successfully synthesized. Abstract : A novel type of high- χ block copolymer, polystyrene- block -polycarbonate (PS- b -PC), which contains an active –NH– group on the polymer backbone between the PS block and the PC block, has been successfully synthesized. Vertical micro-phase separation can be successfully achieved on Si substrates with neutral-layer-free materials with a pitch of 16.8 nm. Water contact angle experiments indicate that PS and PC have approximate surface energy values on Si substrates. A hydrogen bond mechanism has been proposed for the formation of a periodic and lamella-forming phase separation structure, with the domains oriented perpendicular to the substrate. A combination of both theory and experimental verification proves that the hydrogen bonding plays a dominant role as a real driving force to promote vertical micro-phase separation in the absence of a neutral layer. Subsequently, the study of a novel block copolymer on four different types of substrate without any neutral layer further confirms that the newly synthesized material enables greater flexibility and potential applications for the fabrication of various nanostructures and functional electronic devices in a simple, cost-effective and efficient way, which is of considerable importance to contemporary and emerging technology applications.